Distinct Contributions of Particle Adsorption and Interfacial Compression to the Surface Pressure of a Fluid Interface - Fu, Yu (Langmuir : the ACS journal of surfaces and colloids, 2024)
Particle-laden interfaces stabilize emulsions and foams and can serve as a platform for multiscale materials. Favorable wetting of a particle to a fluid interface reduces the apparent interfacial tension through area replacement with a linear relationship between the apparent surface pressure and the particle area fraction. The area replacement model is widely employed, often up to particle area fraction reaching the maximum hexagonal packing. However, data directly supporting the area replacement model are limited, and the description ignores contributions from particle-particle interactions and does not describe the surface pressure during the compression of a particle-laden interface. This work reports on the direct validation of the area replacement model through the direct measurement of the adsorption energy, surface pressure, and area fraction of adsorbed particles. Experiments combining tensiometry and confocal imaging during the adsorption of colloidal particles to the oil-water interface confirm the area replacement model within the observed range of area fraction, but only when the drop area is kept constant. Results highlight the importance of keeping the droplet area constant during particle adsorption to extract the adsorbed amount from tensiometry experiments. As particles adsorb to the interface, the droplet area tends to change and compresses or expands the interface. This change in area is associated with an increase in area fraction at nearly constant surface pressure, which deviates from the area replacement model. In contrast to particle adsorption, slow compression of the fluid interface leads to a negligible change in surface pressure up to an area fraction of η ∼ 0.26 for the materials systems investigated. Increase in surface pressure during compression is due to particle-particle interactions, while compression at higher strain rates introduces additional contributions from interfacial rheology